COMPARISON OF PERCUTANEOUS PINNING WITH CASTING IN SUPRACONDYLAR HUMERAL FRACTURES IN CHILDREN - Khan, Mohammad Shoaib; Sultan, Shahid; Ali, Mian Amjad; Khan, Alamzeb; Younis, Mohammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: In Children Supracondylar fracture of humerus is one of the most common fractures in first decade of life. There are various treatment modalities for this fracture i.e. Close reduction and casting, open reduction and internal fixation, skeletal traction and Percutaneous Pinning. This study was conducted to know the outcome of Percutaneous Pinning in the management of displaced supracondylar humeral fracture in children and to compare the results with close reduction and castings and published literature. Methods:This descriptive study was conducted in Orthopaedic department of Ayub Teaching Hospital Abbottabad and Lady Reading Hospital, Peshawar from January 2002 till December 2003 on 40 children. Patients included were of either gender with age range from 3 to 12 years with displaced supracondylar fracture presenting within 72 hours of injury. Two treatment modalities were studied for comparison. Cross k-wires fixation through each humeral condyle was done after closed reduction of fracture under image intensifier in general anesthesia. Casting/Backslab was applied after reduction of fracture without image intensifier under anesthesia or analgesia. Out come measures were according to Flynn criteria that are functional and cosmetic factor which is based on loss of elbow motion and carrying angle in degrees respectively. Results: Cross percutaneous pinning gave excellent results in 13 (65%), good outcome in 4(20%) and poor outcome in 3(15 %) patients. While patients treated with close reduction and casting showed excellent results in 4 patients (20%), good in 8 patients (40%), fair in 2 patients (10%) and poor in 6 patients (30%). Conclusion: Closed reduction and cross percutaneous pinning for displaced supracondylar humerus fractures in children is safe, cost and time effective method and gives stable fixation with excellent outcome as compared to close reduction and casting. Keywords: Percutaneous Pinning, Supracondylar fracture, Humerus fractures, close reduction